Measurements and analysis of the radar cross section of chaff dipoles - Balleri, Alessio; Butters, Brian (Institution of Engineering and Technology (IET), 2024)
A free space test method to measure the Radar Cross Section (RCS) of single dipole elements is presented. The method is such that dipoles can be measured over a large range of frequencies, in free space and without the need of an anechoic chamber. The setup employs with a Vector Network Analyser (VNA) synchronised to a rotating turntable that controls the position of the transmitting and receiving antennas and the polarisation of the irradiated electric field. Measurements are collected for chaff dipoles made of copper wire, microwire and aluminised glass, from 5 to 11 GHz, to allow a comparison of chaff RCS properties with respect to chaff material and method of fabrication. Measurements of the copper wire chaff also allowed a comparison with existing theoretical predictions of chaff reflectivity. An analysis and a comparison of the results is presented. Results show that the experimental trends of the chaff RCS curves agree with the theoretical RCS curves for perfectly conducting wires. They also show that copper wire provides the strongest reflective chaff followed by the aluminised glass and the microwire.
Keywords: Networking & Telecommunications; 4006 Communications engineering; electronic countermeasures; radar cross-sections